To find which expression is equivalent to \(9x^2 - 25\) using the Distributive Property, we can recognize that \(9x^2 - 25\) is a difference of squares. It can be factored using the formula \(a^2 - b^2 = (a + b)(a - b)\).
In this case, we can identify:
- \(a^2 = 9x^2\) which means \(a = 3x\),
- \(b^2 = 25\) which means \(b = 5\).
Therefore, we can rewrite \(9x^2 - 25\) as: \[ (3x)^2 - (5)^2 = (3x + 5)(3x - 5). \]
So, the expression that is equivalent to \(9x^2 - 25\) is:
\[ (3x + 5)(3x - 5). \]
Thus, the correct response is:
(3x+5)(3x−5).